The upper limb movement recovery: parallels between the patients somatotypes - S. N. Derevtsova (National Electronic Information Consortium (NEICON), 2020)
Study objective: to establish the correlation between the paretic hand movement recovery in post-stroke patients in the stroke late residual period and the patients' somatotypes.Materials and methods. The study involved 91 people in the second period of adulthood (53 men, 38 women), somatotyping was performed according to the W.L. Rees - H. Eysenck method. Results. Statistically significant differences in the upper paretic limb movement range recovery were found in men and women in accordance with the body type. Conclusions. The highest percentage of normal movement range was recorded in the limbs' proximal joints of the (shoulder) during movements around the frontal and sagittal axes. The volume of rotational movements as a percentage of the norm was less by 13-17%. The men demonstrated maximum movement recovery of shoulder extension, and this tendency is typical for mature men of asthenic and pyknic somatotypes. The women in all the examined groups demonstrated the minimal increase in the movement ranges in the shoulder and elbow joints.